Specialized Software-Model Complex for Assessing Security of Lightweight Combat Vehicles and Its Application in Planning of Combat Operations - Dudar, Ye. Ye. (Visnyk of Vinnytsia Politechnical Institute, 2017)
The paper presents the results of the analysis of losses of lightweight combat vehicles from various weapons, examines ways to increase the level of protection of machines of this class, and also defines the order of a specialized program-model complex, which is based on an improved method of constructing of application of three-dimensional tactical diagrams of bullet resistance for solving tactical tasks.